The Facial Expressive Action Stimulus Test. A test battery for the assessment of face memory, face and object perception, configuration processing, and facial expression recognition - de Gelder, Beatrice; Huis in ‘t Veld, Elisabeth M. J.; Van den Stock, Jan (Frontiers in Psychology, 2015)
There are many ways to assess face perception skills. In this study, we describe a novel task battery FEAST (Facial Expression Action Stimulus Test) developed to test recognition of identity and expressions of human faces as well as stimulus control categories. The FEAST consists of a neutral and emotional face memory task, a face and object identity matching task, a face and house part-to-whole matching task, and a human and animal facial expression matching task. The identity and part-to-whole matching tasks contain both upright and inverted conditions. The results provide reference data of a healthy sample of controls in two age groups for future users of the FEAST.